The causal association between gut microbiota and postpartum depression: a two-sample Mendelian randomization study - Jin, Wenjun; Li, Bo; Wang, Lijun; Zhu, Lin; Chai, Songhao; Hou, Rui (Frontiers in Microbiology, 2024)
Background: An escalating body of clinical trials and observational studies hints at a plausible link between gut flora and postpartum depression (PPD). The definitive causal dynamics between these two entities remain shrouded in ambiguity. Therefore, in this study, we employed the two-sample Mendelian randomization approach to ascertain the causal link between gut microbiota and PPD.Methods: Summary-level GWAS data related to the human gut microbiota were obtained from the international consortium MiBioGen and the Dutch Microbiome Project (species). For PPD, GWAS data were derived from the FinnGen biobank, consisting 57,604 cases and 596,601 controls. The inverse variance weighted method (IVW) as the cornerstone of our analytical approach. Subsequent to this, a comprehensive suite of tests for pleiotropy and heterogeneity were conducted to ensure the reliability and robustness of our findings.Results: We identified twelve bacterial taxa associated with the risk of PPD. Veillonellaceae, Ruminococcaceae UCG 011, Bifidobacterium adolescentis, Paraprevotella clara, Clostridium leptum, Eubacterium siraeum, Coprococcus catus exhibited an inversely associated with the risk of PPD. Alphaproteobacteria, Roseburia, FamilyXIIIAD3011group，Alistipes onderdonkii， Bilophila wadsworthiashowed a positive correlation with the risk of PPD.The GWAS data derived from the MiBioGen consortium, DMP, and FinnGen consortium, may introduce selection bias. Moreover, the data primarily originates from European populations, hence extrapolating these results to diverse populations should be approached with caution. The etiological factors behind PPD remain enigmatic, alluding to the existence of potential undisclosed confounders.Based on this MR analysis, we found a causal relationship between certain gut microbial communities and PPD. Future clinical studies can further explore the treatment of PPD through the combined use of microorganisms. This not only offers insights into the pathogenesis of PPD but also lays the foundation for utilizing gut microbiota as biotherapeutics in treating neurological disorders.